TINDAK TUTUR ILOKUSI DALAM NOVEL ANGKASA DAN 56 HARI KARYA DESTASHYA WDP (RAVINKYU - Patricia Sianturi; Antonius Totok Priyadi; Ahmad Rabi'ul Muzzamil (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the illocutionary speech acts found in the novelAngkasa dan 56 Hari by Destashya WDP (Ravinkyu). This research employed adescriptive method with a qualitative approach. The data source was the novelAngkasa dan 56 Hari by Destashya WDP (Ravinkyu), while the data consisted ofwords, phrases, and sentences containing illocutionary speech acts. Data werecollected through documentation, reading, and note-taking techniques. Theresearcher served as the primary research instrument. Data validity wasestablished through persistent observation and reference adequacy. Data analysisinvolved identifying, classifying, and analyzing the collected data. The findingsrevealed four categories of illocutionary speech acts. Assertive speech acts wereidentified in 37 utterances, consisting of 34 statements, one report, and twoexpressions of opinion. Directive speech acts appeared in 38 utterances, including13 requests, 19 commands, one plea, and five suggestions. Commissive speechacts comprised two utterances, both functioning as offers. Expressive speech actswere found in 16 utterances, including eight expressions of gratitude, threeapologies, and five compliments. These findings were implemented in the form ofa teaching module for